Classical Approaches to the Study of Religion Aims, Methods and Theories of Research. Introduction and Anthology - Waardenburg, Jean Jacques 1930-2015 (Tubingen De Gruyter, 2011)
Intro -- Preface -- Introduction View Of A Hundred Years' Study Of Religion -- Preliminary -- Historical Survey -- Introduction: Up To The Middle Of The 19Th Century -- 1. The Study Of Religion Established As An Autonomous Discipline -- 2. Connections With Other Disciplines -- 3. Religion As A Special Subject Of Research -- 4. Later Contributions From Other Disciplines -- 5. Perspectives Of A Phenomenological Study Of Religion -- Looking Back -- Anthology -- Introductory Note -- Part 1: The Study Of Religion Established As An Autonomous Discipline -- 1. F. Max MÜller -- Biography -- Plea For A Science Of Religion (From Chips From A German Workshop) -- The Comparative Study Of Religions (From Introduction To The Science Of Religion) -- 2. Cornelis P. Tiele -- Biography -- 'Elements Of The Science Of Religion' (From Elements Of The Science Of Religion, Vols. I And Ii) -- 3. Pierre D. Chantepie De La Saussaye -- Biography -- 'The Science Of Religion' (From Manual Of The Science Of Religion) -- Phenomenology Of Religion (From Manual Of The Science Of Religion) -- Part 2: Connections With Other Disciplines -- 4. Johann J. Bachofen -- Biography -- 'Symbol And Myth' (From Myth, Religion And Mother Right) -- Matriarchy And Religion (From Myth, Religion And Mother Right) -- 5. Ernest Renan -- Biography -- Vindication Of A Critical Mind (From Studies Of Religious History) -- 6. N. D. Fustel De Coulanges -- Biography -- 'The Necessity Of Studying The Earliest Beliefs Of The Ancients In Order To Understand Their Institutions' (From The Ancient City) -- 7. Julius Wellhausen -- Biography -- Historical Research On The Pentateuch (From Prolegomena To The History Of Ancient Israel) -- 8. William Robertson Smith -- Biography -- The Study Of The Religion Of The Semites (From Lectures On The Religion Of The Semites) -- 9. Friedrich C. G. Delitzsch -- Biography.
""â€?The Tabu-Mana Formula As A Minimum Definition Of Religionâ€? ""
Description based upon print version of record
Keywords: Religion ; Study and teaching ; History ; 19th century; Religion ; Study and teaching ; History ; 20th century; Electronic books; Electronic books